2003
DOI: 10.1046/j.1365-2958.2003.03717.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of thymidine kinase from Ureaplasma urealyticum: nucleoside analogues as potent inhibitors of mycoplasma growth

Abstract: SummaryUreaplasma urealyticum ( U. urealyticum ), belonging to the class Mollicutes, is a human pathogen colonizing the urogenital tract and causes among other things respiratory diseases in premature infants. We have studied the salvage of pyrimidine deoxynucleosides in U. urealyticum and cloned a key salvage enzyme, thymidine kinase (TK) from U. urealyticum . Recombinant Uu -TK was expressed in E. coli , purified and characterized with regards to substrate specificity and feedback inhibition. Uu -TK efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 36 publications
(47 reference statements)
2
52
0
Order By: Relevance
“…Finally, the sensitivity of E. coli to FIAU, coupled with the uptake of FIAU by several other bacteria, suggests that TK substrates could be used not only for imaging bacteria but also for therapy. Indeed, it has been shown that nucleoside analogues are potent inhibitors of the growth of mycoplasma and mycobacterial strains (26,27). Recognition of the widespread presence and unique substrate specificities of bacterial TKs may therefore prove useful for the design of novel diagnostic as well as therapeutic modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the sensitivity of E. coli to FIAU, coupled with the uptake of FIAU by several other bacteria, suggests that TK substrates could be used not only for imaging bacteria but also for therapy. Indeed, it has been shown that nucleoside analogues are potent inhibitors of the growth of mycoplasma and mycobacterial strains (26,27). Recognition of the widespread presence and unique substrate specificities of bacterial TKs may therefore prove useful for the design of novel diagnostic as well as therapeutic modalities.…”
Section: Discussionmentioning
confidence: 99%
“…21. For production of selenomethionine (SeMet)-substituted Uu-TK, the Uu-TK construct was transformed into the chemical competent, methionine auxotrophic E. coli strain B834(DE3) (Novagen).…”
Section: Methodsmentioning
confidence: 99%
“…The SelenoMet media was changed to contain SeMet before induction with 1 mM isopropyl ␤-D-galactopyranoside for 6 h at 25°C, and SeMet-substituted Uu-TK was purified essentially as described in ref. 21.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations